OC-152 "Expecting the unexpected": a review of extracolonic findings found at ct colonography. (28th May 2012) - Owen, H M; Foulkes, R; Billings, P; Chandran, P; Corr, C
Abstract : Introduction: The aim of this paper is to report the high prevalence of important extracolonic findings, including cancer, at CT colonography. Methods: Using the PACS system all CT colonograms performed for symptomatic indications between December 2006 and June 2011 were retrieved as part of our ongoing audit. Extracolonic findings were identified and analysed. They were categorised into extracolonic malignancies, benign and important benign findings which were findings that required further investigation or management. Results: 830 patients underwent CT Colonography during this time period (518 females, 313 males, average age 74). 85 colonic cancers were identified and 103 patients had colonic polyps with or without extracolonic findings. Extracolonic abnormalities were found in 383 patients (46%). Of those patients with extracolonic findings 9% had extracolonic malignancies, 26% had important extracolonic findings requiring further investigation, management or referral and 65% were benign incidental findings requiring no further follow-up. The most common benign incidental finding was renal cysts and the most common extracolonic malignancy was renal carcinoma. Abstract OC-152 table 1 gives a summary of the number of extracolonic findings identified with the highest prevalence. Conclusion: CT Colonography has the potential to pick up cancers and other life threatening lesions such as large non ruptured AAA at a preclinical stage. While we acknowledge that extracolonic abnormalities are common with the correct planning and management we do not believe that this should necessarily increase the number of further unnecessary investigations or costs. Competing interests: None declared.